The Employment Impact of Emerging Digital Technologies - Ekaterina Prytkova; Fabien Petit; Deyu Li; Sugat Chaturvedi; Tommaso Ciarli (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper measures the exposure of industries and occupations to 40 digital technologies that emerged over the past decade and estimates their impact on European employment. Using a novel approach that leverages sentence transformers, we calculate exposure scores based on the semantic similarity between patents and ISCO-08/NACE Rev.2 classifications to construct an open–access database, 'TechXposure'. By combining our data with a shift–share approach, we instrument the regional exposure to emerging digital technologies to estimate their employment impact across European regions. We find an overall positive effect of emerging digital technologies on employment, with a one-standard-deviation increase in regional exposure leading to a 1.069 percentage point increase in the employment-to-population ratio. However, upon examining the individual effects of these technologies, we find that smart agriculture, the internet of things, industrial and mobile robots, digital advertising, mobile payment, electronic messaging, cloud storage, social network technologies, and machine learning negatively impact regional employment.
Keywords: C81; O31; O33; O34; J24; O52; R23; 330; occupation exposure; industry exposure; text as data; natural language processing; sentence transformers; emerging digital technologies; automation; employment